Crop Improvement: Where Are We Now? - Pierre Sourdille; Pierre Devaux (Biology, 2022)
Improving the production of all crops is crucial to meeting the challenge of the growing needs related to the simultaneous increase in the world population and demands from farmers and end-users [...]